Comparison of Excision and Graft of Early-Onset and Late-Onset Burns: A Systematic Review - Ni Putu Tiza Murtia Margha Margha; Gde Dedy Andika (Green Publisher Indonesia, 2025)
Autologous skin grafts are generally considered the gold standard for covering large skin defects in burn patients. Full-thickness skin grafts produce the best aesthetic and functional results in burn reconstruction. Many techniques and adjustments have been developed over time, and even the optimal timing for intervention remains a debatable topic. This article will discuss the comparison of excision and graft actions for early-onset and late-onset burns. This research used the PRISMA 2020 standard, ensuring that all requirements were met. The studies included in this article were published between 2015 and 2025 and were sourced from the Google Scholar database and other web resources. The search yielded nine studies relevant to the research objectives from the last ten years. Relevant articles generally suggest that early intervention can provide longer-lasting benefits and lower treatment costs, albeit inconsistently in terms of complications during treatment—for example, the need for transfusions and shock events. Early skin graft and excision management can reduce both treatment duration and cost. Research outcomes based on patient satisfaction showed that interventions performed at early onset resulted in higher satisfaction.